Investment, subsidies, and pro-poor growth in rural India - Fan, Shenggen; Gulati, Ashok; Thorat, Sukhadeo (International Food Policy Research Institute, 2007)
This paper reviews the trends in government subsidies and investments in and for Indian agriculture; develops a conceptual framework and model to assess the impact of various subsidies and investments on agricultural growth and poverty reduction; and, presents several reform options with regard to re-prioritizing government spending and improving institutions and governance. There are three major findings. First, initial subsidies in credit, fertilizer, and irrigation have been crucial for small farmers to adopt new technologies. Small farms are often losers in the initial adoption stage of a new technology since prices of the agricultural products are typically being pushed down by greater supply of products from large farms, which adopted the new technology. But as more and more farmers have adopted HYV, continued subsidies have led to inefficiency of the overall economy. Second, agricultural research, education, and rural roads are the three most effective public spending items in promoting agricultural growth and poverty reduction during all periods. Finally, the trade-off between agricultural growth and poverty reduction is generally small among different types of investments. As for agricultural research, education, and infrastructure development, they have large growth impact and a large poverty reduction impact. Several policy lessons can be drawn. Agricultural input and output subsidies have proved to be unproductive, financially unsustainable, environmentally unfriendly in recent years, and contributed to increased inequality among rural Indian states. To sustain long-term growth in agricultural production, and therefore provide a long-term solution to poverty reduction, the government should cut subsidies of fertilizer, irrigation, power, and credit and increase investments in agricultural research and development, rural infrastructure, and education. Promoting nonfarm opportunities is also important. However, simply reallocating public resources is not the full solution. Reforming institutions can have an equal, if not larger, impact on future agricultural and rural growth and rural poverty reduction.